Major complications after percutaneous biopsy of native or transplanted liver in pediatric patients: a nationwide inpatient database study in Japan - Kayo Ikeda Kurakawa; Akira Okada; Kazuhiko Bessho; Taisuke Jo; Sachiko Ono; Nobuaki Michihata; Ryosuke Kumazawa; Hiroki Matsui; Kiyohide Fushimi; Satoko Yamaguchi; Toshimasa Yamauchi; Masaomi Nangaku; et al. (BMC Gastroenterology, 2022)
Abstract Aim Although major complication rates following percutaneous liver biopsy (PLB) have been reported to be higher in children than in adults, scarce data are available regarding pediatric patients stratified by native and transplanted liver. We aimed to assess the factors associated with major complications after percutaneous biopsy of native or transplanted liver using a nationwide inpatient database. Methods Using the Japanese Diagnosis Procedure Combination database, we retrospectively identified pediatric patients who underwent PLB between 2010 and 2018. We described major complication rates and analyzed factors associated with major complications following PLB, stratified by native and transplanted liver. Results We identified 3584 pediatric PLBs among 1732 patients from 239 hospitals throughout Japan during the study period, including 1310 in the native liver and 2274 in the transplanted liver. Major complications following PLB were observed in 0.5% (n = 18) of the total cases; PLB in the transplanted liver had major complications less frequently than those in the native liver (0.2% vs. 1.0%, p = 0.002). The occurrence of major complications was associated with younger age, liver cancers, unscheduled admission, anemia or coagulation disorders in cases with native liver, while it was associated with younger age alone in cases with transplanted liver. Conclusions The present study, using a nationwide database, found that major complications occurred more frequently in pediatric cases with native liver and identified several factors associated with its major complications.